Experimental Evidence of A2A–D2 Receptor–Receptor Interactions in the Rat and Human Carotid Body - Stocco, Elena; Sfriso, Maria Martina; Borile, Giulia; Contran, Martina; Barbon, Silvia; Romanato, Filippo; Macchi, Veronica; Guidolin, Diego; De Caro, Raffaele; Porzionato, Andrea (Frontiers in Physiology, 2021)
Adenosine A2A receptors (A2AR) and dopamine D2 receptors (D2R) are known to be involved in the physiological response to hypoxia, and their expression/activity may be modulated by chronic sustained or intermittent hypoxia. To date, A2AR and D2R can form transient physical receptor–receptor interactions (RRIs) giving rise to a dynamic equilibrium able to influence ligand binding and signaling, as demonstrated in different native tissues and transfected mammalian cell systems. Given the presence of A2AR and D2R in type I cells, type II cells, and afferent nerve terminals of the carotid body (CB), the aim of this work was to demonstrate here, for the first time, the existence of A2AR–D2R heterodimers by in situ proximity ligation assay (PLA). Our data by PLA analysis and tyrosine hydroxylase/S100 colocalization indicated the formation of A2AR–D2R heterodimers in type I and II cells of the CB; the presence of A2AR–D2R heterodimers also in afferent terminals is also suggested by PLA signal distribution. RRIs could play a role in CB dynamic modifications and plasticity in response to development/aging and environmental stimuli, including chronic intermittent/sustained hypoxia. Exploring other RRIs will allow for a broad comprehension of the regulative mechanisms these interactions preside over, with also possible clinical implications.